MANAGEMENT OF PHYSIOTHERAPY TO INCREASE GAIT SPEED IN PATIENTS WITH KNEE OSTEOARTHRITIS: SINGLE CASE STUDY - Anggraini, Nadya; Perdana, Suryo Saputra; Santoso, Totok Budi; Putri, Thesa Arsita (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Osteoarthritis(OA) is a musculoskeletal disorder that causes changes in the joints progressively slowly and intermittently. Usually, in the field, muscle strengthening exercises are often found that only focus on the agonist's muscle. Whereas antagonistic muscles also play a role and are even more dominant. The most recommended intervention to be able to activate the two muscles is in the form of taskspecific exercises. The basic concept of task-specific exercise itself is muscle coactivation. To be able to see muscle activity being activated, task-specific exercises are combined with visual surface electromyography (SEMG) biofeedback. Case Presentation: the patient is 57-years old woman and works as a housewife. Patient from Solo, Central Java. Examination of the patient was found to have 3 types of causes such as age more than 45 years or more, morning stiffness for less than 30 minutes, and pain when doing activities. Management and Outcomes: Given treatment in the form of task-specific training combined with visual surface electromyography (SEMG) biofeedback to increase the walking speed and functional activity of the patient. Furthermore, the measuring instrument used for walking speed is the 10-meter walking test and WOMAC Discussion: A study revealed that the addition of a visual surface EMG biofeedback component in task-specific functional training had a positive effect on increasing muscle function and strength. The authors assume that the addition of visual biofeedback can have a positive impact on the rehabilitation process. Conclusion: Giving this intervention can provide a statistically significant improvement and can be implemented clinically to increase walking speed in individual patients and this can provide a significant improvement in functional ability in patients with osteoarthritis of the knee.